Ownership: A Perennial Prize or a Fading Goal? A Curation, Framework, and Agenda for Future Research - Lamberton, Cait; Goldsmith, Kelly (Journal of Consumer Research, 2020)
For many, it is difficult to imagine that sharing used clothes with strangers and/or buying low quality, temporary garments could ever be preferable to owning our own. However, new findings from the Journal of Consumer Research suggest there may be contexts in which, and consumers for whom, this may in fact be true. We suggest that, given this work, consumer researchers are uniquely situated to explore whether we have indeed reached the proposed, “End of Ownership” (Perzanowski and Schultz 2017), as it has been known. If so, we must ask what may be gained as the desire for ownership wanes, in addition to what marketers, consumers and society might stand to lose in its absence.